Control of the Root-Knot Nematode (Meloidogyne spp.) on Cucumber by a Liquid Bio-Formulation Containing Chitinolytic Bacteria, Chitin and Their Products - Woo Jong Ha; Young Cheol Kim; Hyunchae Jung; Seur Kee Park (Research in Plant Disease, 2014)
A liquid bio-formulation containing chitinolytic bacteria, chitin and their products was assessed for its potential biological control against root-knot nematodes on cucumber. The bio-formulation was prepared by cultures of three chitinolytic bacteria, Chromobacterium sp. strain C-61, Lysobacter engymogenes and Serratia plymuthica in minimal medium supplemented with chitin. Under pot conditions, the bio-formulation showed better growth of cucumber plants, and less root galls and population density of Meloidogyne spp. than control media without the bio-formulation. In a greenhouse, 75-fold diluted bio-formulations were treated instead of water around cucumber plants through hoses for drip irrigation six times at 5-day intervals from the transplanting date. After 30 and 60 days, the treatment provided about 7% and 10% enhancement in the plant height and about 78% and 69% reduction in population density of Meloidogyne spp. in the rhizosphere, respectively. In addition, the experiments showed that the control effects occurred only in the soils contacted with the bio-formulation. Undiluted bio-formulations were drenched three times at 10-day intervals around cucumber plants severely infested with Meloidogyne spp. The treatment showed about 37% plant enhancement without dead plants compared with 37% death in the untreated control, and about 82% nematode reduction. These results suggest that the bio-formulation can be practically used to control the root-knot nematode on cucumber.